GARDENING-BASED OCCUPATIONAL THERAPY AS AN INTERVENTION TO REDUCE AUDITORY HALLUCINATIONS IN PATIENTS WITH SCHIZOPHRENIA: A CASE REPORT - Fatimah Al-Zahra; Dhia Diana Fitriani; Herliawati; Zulian Effendi (Spectra Clinical Case Reports Journal, 2026)
Mental health disorders, particularly schizophrenia, represent a global health challenge that significantly affects quality of life, productivity, and social functioning. One of the most common symptoms of schizophrenia is auditory hallucinations, which impair daily functioning and increase the risk of harmful behavior. Therefore, nonpharmacological interventions are needed to support symptom management. This case report aimed to implement gardening occupational therapy as an intervention to reduce the level of auditory hallucinations among patients with schizophrenia in the Cendrawasih Ward of Hospital. Three patients with schizophrenia who experienced auditory hallucinations were observed over a seven-day period. Baseline assessment was conducted using interviews, observation, and the Auditory Hallucination Rating Scale (AHRS). Patients received four days of nursing interventions focused on hallucination management, followed by three consecutive days of gardening-based occupational therapy. The therapy was conducted once daily in the hospital’s therapeutic garden, with each session lasting 30–40 minutes. Outcome assessment was performed using the AHRS immediately after completion of the intervention period. The results showed a reduction in hallucination severity in all patients. Two patients who were initially categorized as having severe auditory hallucinations and one patient with moderate auditory hallucinations showed a reduction in AHRS scores, resulting in all patients being classified in the mild category after the intervention. In addition, patients appeared calmer, more focused, and better able to manage hallucinations and interact with their environment. These findings suggest that gardening-based occupational therapy may be an effective complementary intervention for reducing auditory hallucination severity and promoting psychosocial functioning among patients with schizophrenia